Cell lines from imaginal discs of Drosophila melanogaster. - Ui, K.; Ueda, R.; Miyake, T. (In Vitro Cellular and Developmental Biology, 1987)
New cell lines, designated as ML-DmD1-10, were established from dissociated imaginal discs of Drosophila melanogaster. The culture medium was prepared by mixing in a 1:1 ratio Cross and Sang's M3(BF) medium, supplemented with 10% heat inactivated fetal bovine serum (FBS), with the supernatant of a primary embryonic cell culture made in the M3(BF) medium and supplementing this mixture with insulin. One cell line was established in the medium containing larval hemolymph instead of the primary culture supernatant, and another was established in fresh M3(BF) medium supplemented with insulin and FBS. In these mediums, imaginal disc cells first formed aggregates and cellular vesicles within a few weeks followed by the proliferation of thin-layered cells around them after about 1 mo. Ten cell lines have so far been established from two kinds of imaginal discs and disc mixtures. The ploidy of these cell lines was predominantly diploid. Population doubling time was about 50 to 70 h at 3 to 10 mo. after initiation of the culture. When the cell aggregates formed in vitro were implanted in metamorphosing larvae, they differentiated at high frequency into adult cuticular structures in the early phase of the primary culture. This differentiation of aggregates was also observed, though at low frequency, in a culture maintained by dilution-transfer for 6 to 15 mo. in vitro.